TRANSMISI VERTIKAL HARGA BERAS DI PROPINSI LAMPUNG - Lantarsih, Retno; Hadi Darwanto, Dwidjono; Handoyo Mulyo, Jangkung (MAPETA, 2010)
Price behavior is an indicator for market efficiency. The reseach is conducted: (i) to examine the relationships between riil price for rice at retail level and riil price for rough rice at producer level, (ii) to examine the relationships between riil price for rice at retail level and riil price for impor rice. The causality is analysed by error correction representation, and the asymmetry of price transmmision is analysed by error correction model approach. It is used monthly time series data from 1998 – 2008. Results of the research show that: (i) the riil price for rice at retail level is integrated to the riil price for rough rice at producer level in the longrun; (ii) there is a causality direction from riil price for rice at retail level to riil price for rough rice at producer level, and no reverse, (iii) the price transmmision of relationship between riil price for rice at retail level and riil price for rough rice at producer level is asymmetry. Price adjusment of rough rice at raising price is slower than at falling price.Key words: Asymmetry Price Transmission, Rice, Lampung Province